Drought Stress in Grain Legumes during Reproduction and Grain Filling. (22nd January 2016) - Farooq, M.; Gogoi, N.; Barthakur, S.; Baroowa, B.; Bharadwaj, N.; Alghamdi, S. S.; Siddique, K. H. M.
Abstract: Water scarcity is a major constraint limiting grain legume production particularly in the arid and semi‐arid tropics. Different climate models have predicted changes in rainfall distribution and frequent drought spells for the future. Although drought impedes the productivity of grain legumes at all growth stages, its occurrence during reproductive and grain development stages (terminal drought) is more critical and usually results in significant loss in grain yield. However, the extent of yield loss depends on the duration and intensity of the stress. A reduction in the rate of net photosynthesis, and poor grain set and grain development are the principal reasons for terminal drought‐induced loss in grain yield. Insight into the impact and resistance mechanism of terminal drought is required for effective crop improvement programmes aiming to improve resistance to terminal drought in grain legumes. In this article, the impact of terminal drought on leaf development and senescence, light harvesting and carbon fixation, and grain development and grain composition is discussed. The mechanisms of resistance, management options, and innovative breeding and functional genomics strategies to improve resistance to terminal drought in grain legumes are also discussed.